PEMBERDAYAAN DAN PENDAMPINGAN MASYARAKAT MELALUI PELATIHAN PENGOLAHAN DAN PEMANFAATAN PRODUK OLAHAN NANAS DI DESA SUNGAI SUNGAI RAYA DALAM - Sumiyati Sumiyati; Supiana Supiana (Jurnal Buletin Al-Ribaath, 2018)
Desa Sungai Raya Dalam has an abundant potential for pineapple plantations. Pineapple is a kind of tropical fruit and vegetable plant with approximate numbers of production reaching 10,000 tons. However, the large numbers of production had not been utilized optimally by the community, though there are many benefits that can be obtained from pineapple. The purpose of this activity was to provide counseling and socialization to the community particularly to housewives in Sungai Raya Dalam Village, Tanggok Parit Village, and Bunga Raya Hamlet, RT. 016, RW. 07 on the alternative processing of pineapple into various processed cakes.